Analysis of Four Dispersion Vectors in Inland Waters: The Case of the Invading Bivalves in South America - Belz, cCarlos E. (2012)
Fil: Belz, cCarlos E.. Universidade Federal do Paraná (CEHPAR). Curitiba. Paraná; Brazil